2006
DOI: 10.1136/bmj.38933.585764.ae
|View full text |Cite
|
Sign up to set email alerts
|

Post-infective and chronic fatigue syndromes precipitated by viral and non-viral pathogens: prospective cohort study

Abstract: Objective To delineate the risk factors, symptom patterns, and longitudinal course of prolonged illnesses after a variety of acute infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
553
3
19

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 692 publications
(646 citation statements)
references
References 32 publications
(33 reference statements)
37
553
3
19
Order By: Relevance
“…A recent study showed that post-infective fatigue syndrome could be predicted by the severity of the acute illness, and its incidence was similar after the different infections [43]. In this cohort, the case rate for provisional post-infective fatigue syndrome was 35% (87/250) at six weeks, 27% (67/250) at three months, and 9% (22/250) at 12 months [43]; rates similar to those reported in patients treated for erythema migrans (see above) [13]. The mechanisms that are triggered during the acute illness and that sustain the persistent symptoms in post-infective fatigue syndrome are currently unknown.…”
Section: The Possible Causes Of Post-lyme Disease Symptomsmentioning
confidence: 99%
“…A recent study showed that post-infective fatigue syndrome could be predicted by the severity of the acute illness, and its incidence was similar after the different infections [43]. In this cohort, the case rate for provisional post-infective fatigue syndrome was 35% (87/250) at six weeks, 27% (67/250) at three months, and 9% (22/250) at 12 months [43]; rates similar to those reported in patients treated for erythema migrans (see above) [13]. The mechanisms that are triggered during the acute illness and that sustain the persistent symptoms in post-infective fatigue syndrome are currently unknown.…”
Section: The Possible Causes Of Post-lyme Disease Symptomsmentioning
confidence: 99%
“…Self-report measures of symptom severity and functional impairment were recorded at regular intervals over 12 months as described. 2 A severity index of the acute illness was based on the score in the SOMA subscale of the SPHERE questionnaire, which has been shown to correlate with significant disability due to illness and the need for medical care in this cohort. The duration of illness was designated as the number of days from onset to resolution of significant illness on the SOMA subscale (reflected by a score of three or more out of the possible 12 on the scale).…”
Section: Resultsmentioning
confidence: 99%
“…A protracted clinical course marked by fatigue is common. 2 However, subclinical infections are at least four times more common than overt illness.…”
Section: Introductionmentioning
confidence: 99%
“…Los estados de fatiga prolongada después de las infecciones son comunes y pueden ser incapacitantes para las personas que los padecen. En cuanto a su duración, se ha reportado que pueden persistir durante 12 meses o más, y que pueden convertirse en estados de fatiga crónica (26,33). Aunque la fase aguda de las infecciones puede variar, la fatiga se presenta con características clínicas similares en estas enfermedades (33).…”
Section: Discussionunclassified
“…En cuanto a su duración, se ha reportado que pueden persistir durante 12 meses o más, y que pueden convertirse en estados de fatiga crónica (26,33). Aunque la fase aguda de las infecciones puede variar, la fatiga se presenta con características clínicas similares en estas enfermedades (33). Su etiología aún no se ha descrito con precisión, de la fase aguda, entre los cuales predominó el cansancio físico (65,6 %), la cefalea (37,5 %), el insomnio (31,3 %), el mareo, el cansancio mental (25 %) y el dolor muscular (18,8 %).…”
Section: Discussionunclassified